2006
DOI: 10.1007/s00500-006-0139-6
|View full text |Cite
|
Sign up to set email alerts
|

Diversity-adaptive parallel memetic algorithm for solving large scale combinatorial optimization problems

Abstract: Parallel memetic algorithms (PMAs) are a class of modern parallel meta-heuristics that combine evolutionary algorithms, local search, parallel and distributed computing technologies for global optimization. Recent studies on PMAs for large-scale complex combinatorial optimization problems have shown that they converge to high quality solutions significantly faster than canonical GAs and MAs. However, the use of local learning for every individual throughout the PMA search can be a very computationally intensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(66 citation statements)
references
References 26 publications
0
66
0
Order By: Relevance
“…MAs aim to balance the exploration and exploitation capabilities of both genetic algorithms and local search. Many researchers already highlighted the effectiveness of integrating meme(s) into evolutionary algorithms for solving complex optimization problems based on various frameworks [1,2,13,30,38,40,48,53,54]. In a canonical MA, a prefixed single meme is employed after mutation and evaluation steps of a GA. Obviously, a variety of memes might be designed for solving a specific problem.…”
Section: 2 Memes and Self-generationmentioning
confidence: 99%
“…MAs aim to balance the exploration and exploitation capabilities of both genetic algorithms and local search. Many researchers already highlighted the effectiveness of integrating meme(s) into evolutionary algorithms for solving complex optimization problems based on various frameworks [1,2,13,30,38,40,48,53,54]. In a canonical MA, a prefixed single meme is employed after mutation and evaluation steps of a GA. Obviously, a variety of memes might be designed for solving a specific problem.…”
Section: 2 Memes and Self-generationmentioning
confidence: 99%
“…In [4] the classification of coordination methods has been extended and updated. The following four categories have been identified: 1) Adaptive Hyper-heuristic, where heuristic rules are employed (e.g., [8], [9], [10], [11]); 2) MetaLamarckian learning defined in [12], where the activation of the memes depends on their success, see also [13], [14], [15]; 3) Self-Adaptive and Co-Evolutionary, where the rules coordinating the memes are evolving in parallel with the candidate solutions of the optimization problem or encoded within the solution, see [16], [17], [18], [19]; and 4) Fitness DiversityAdaptive, where the activation of the memes depends on a measure of the diversity (e.g., [20], [21], [6], [22], [23]). As a general idea, the algorithmic designer attempts to have a system which performs the coordination automatically.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, MAs have been well used across a wide range of problem domains. A lot of studies have demonstrated that MAs converge to high-quality solutions more efficiently than their conventional counterparts in many realworld applications [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. MAs have also been applied in the image processing field [33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%